Pengaruh Literasi Dan Tingkat Religiusitas Terhadap Minat Berwakaf Uang (Studi Kasus: Masyarakat Kabupaten Bima) - Maulana Syarif Hidayatullah; Mujakir (Badan Wakaf Indonesia, 2022)
This study aims to determine the effect of literacy and the level of religiosity on the interest in cash waqf in the people of Bima district. The data and information used in this study used primary data obtained from the results of filling out the questionnaire. The type of data used is quantitative and uses multiple linear regression analysis with the sampling technique using Simple Random Sampling. The results showed that the literacy and religiosity variables each had a significant influence on the interest in cash waqf in the people of Bima district.